2002
DOI: 10.1016/s0006-3495(02)75459-3
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Distributions for Cytochrome c on Polar and Nonpolar Interfaces by Total Internal Reflection Fluorescence

Abstract: The formation of chemisorbed monolayers of yeast cytochrome c on both uncharged polar and nonpolar soft surfaces of organic self-assembled monolayers (SAM) on solid inorganic substrates was followed in situ by polarized total internal reflection fluorescence. Two types of nonpolar surfaces and one type of uncharged polar surface were used. The first type of nonpolar surface contained only thiol endgroups, while the other was composed of a mixture of thiol and methyl endgroups. The uncharged polar surface was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 16 publications
3
37
0
Order By: Relevance
“…For example, Balakrishnan [136] showed the influence of spatial curvature effects on FCS of molecules diffusing within membranes, and Chirico et al [137] modelled a similar although small effect for dyes in solution that was earlier observed by Osborne et al [138]. The final result of an FCS experiment is the autocorrelation function that is condensed out of a large file of recorded fluorescence intensities.…”
Section: Fluorescence Correlation Spectroscopymentioning
confidence: 73%
See 2 more Smart Citations
“…For example, Balakrishnan [136] showed the influence of spatial curvature effects on FCS of molecules diffusing within membranes, and Chirico et al [137] modelled a similar although small effect for dyes in solution that was earlier observed by Osborne et al [138]. The final result of an FCS experiment is the autocorrelation function that is condensed out of a large file of recorded fluorescence intensities.…”
Section: Fluorescence Correlation Spectroscopymentioning
confidence: 73%
“…Recent advances in ultra-sensitive instrumentation have allowed the detection of individual atoms and molecules in solids [133,134], on surfaces [135,136], and in the condensed phase [137,138] using laser-induced fluorescence. In particular, single molecule detection in the condensed phase enables scientists to explore new frontiers in many scientific disciplines, such as chemistry, molecular biology, molecular medicine and nanostructure materials.…”
Section: Single Molecule Fluorescencementioning
confidence: 99%
See 1 more Smart Citation
“…The most common covalent immobilisation approach is to form an amide linkage between a carboxyl‐terminated (−COOH) self‐assembled monolayer (SAM) and lysine residues (LYS‐73, LYS‐86 or LYS‐87) of the cyt c . However, a major issue with amide linkages is the lack of chemoselectivity for specific lysine residues . Figure a highlights all lysines present on iso‐1 cyt c , where poor chemoselectivity can result in cyt c conjugation to the surface with a number of orientations .…”
Section: Introductionmentioning
confidence: 99%
“…[29] The properties of vectorially orientated YCC, chemisorbed via Cys102 at thiol-modified surfaces, have been extensively studied. [30][31][32][33] Scanning probe microscopy has shown that YCC can be immobilized directly on gold via Cys102. [34][35][36] Moreover, we have shown that YCC, vectorially chemisorbed on gold, exhibits very fast, reversible interfacial electron transfer and retains its native functionality, that is, the ability to interact with redox enzymes in solution.…”
Section: Introductionmentioning
confidence: 99%